Evaluation of Visual Control Effect on Quiet Stance Stability in Early Stage Parkinson`s Disease, Linear and Nonlinear Approaches - Mina Mirahmadi; Mohammad Taghi Karimi; Vahid Shaygan Nejad; Javid Mostamand (Vesnu Publications, 2014)
Introduction: Parkinson`s disease (PD) is a chronic disorder of basal ganglia with cardinal signs of resting tremor, bradykinesia, rigidity and postural instability. Various studies have evaluated quiet stance postural stability in mild PD but as the authors know there is no consensus on this issue. Therefore, the aim of this study was to evaluate stance stability of the subjects at early stage of PD with both linear and non-linear approaches. Moreover, it was aimed to find the effect of visual control on quiet stance postural control in the patients affected by this disorder. Materials and Methods: 17 patients at early stage of Parkinson disease (H&Y scale: 1) and 17 normal matched subjects were recruited in this study. They were asked to stand on the force plate for 1 minute and postural sway was recorded in two conditions (Opened Eyes and Closed Eyes) with three trials of each condition. The postural stability were evaluated with the linear COP measures of excursion; path length; velocity; Root Mean Square (RMS) and one nonlinear parameter, Approximate Entropy (ApEn) in both directions of anteroposterior (AP) and mediolateral (ML). A 2×2 mixed ANOVA was used for final analysis. Results: The mean values of COP path length and velocity in AP and ML directions were significantly more in PD group in comparison with control group (P˃ 0/028) and increased significantly with eye closure in both groups (P˃ 0/031). The mean values of COP ApEn in AP and ML directions were more in PD patients but the difference was not significant, however they increased significantly after eye closure in both groups (P˃ 0/025). Conclusion: Early stage PD patients have a subclinical postural instability based on both linear and nonlinear COP measures but their dependency to visual sense is not more than healthy subjects to control quiet stance stability.